Women and their Journey to Self-Empowerment: A Case Study of Six Indonesian Female Migrant Domestic Workers - Pusparani, Safira Prabawidya; Soetjipto, Ani Widyani (Jurnal Perempuan, 2017)
In Indonesia, female migrant domestic workers’ representations tend to contain negative meanings. Although they are named as “heroes of development”, but their position is nothing more than a commodity for the country. Such treatment makes female migrant domestic workers becomes vulnerable to violence and exploitation by employers, agents, andgovernment staff. Nevertheless, there is an alternative narrative that is rarely highlighted in literature or media, namely the representation of female migrant domestic workers as powerful actors. This paper seeks to fill in that alternative narrative by highlighting the agencies did by these six female migrant domestic workers. The author believes that by using the standpoint feminism perspective to analyze the struggle of these six female migrant domestic workers in empowering themselves after the oppression, it can be seen that agency has been manifested by female migrant domestic workers during the migration process. This study reveals the efforts of female migrant domestic workers to manifest their empowerment through migration decisions in the middle of patriarchal structures, their ability to resist structures with activism, and become agents of development and change for their communities.